2022
DOI: 10.3390/pharmaceutics14122774
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate Kinase M2 Promotes Hair Regeneration by Connecting Metabolic and Wnt/β-Catenin Signaling

Abstract: Hair follicle stem cells (HFSCs) utilize glycolytic metabolism during their activation and anagen induction. However, the role of pyruvate kinase M2 (PKM2), which catalyzes the final step of glycolysis, in hair regeneration has not been elucidated. In this study, we investigated the expression pattern and activity of PKM2 during the depilation-induced anagen progression in mice. We found that TEPP-46, a selective activator of PKM2, enhanced hair re-growth and proliferation of HFSCs. PKM2 expression was increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…PKM2 is a key enzyme in the glycolysis pathway that produces the necessary bioenergetics for the repeated cycles of self-renewal and differentiation required by stem cells. PKM2 was elevated during the transition to the anagen phase in hair follicles, and levels remained elevated in this phase, while lower levels were found in the androgenic mouse model [ 71 ]. A reduced level of PKM2 was observed in testosterone-treated mice, while elevated expression of this protein occurred in the androgenic mice, regrowing hair after treatment with minoxidil (1%, w / w ), AA in ethanol (1%), and AA–TF#15 (1%).…”
Section: Discussionmentioning
confidence: 99%
“…PKM2 is a key enzyme in the glycolysis pathway that produces the necessary bioenergetics for the repeated cycles of self-renewal and differentiation required by stem cells. PKM2 was elevated during the transition to the anagen phase in hair follicles, and levels remained elevated in this phase, while lower levels were found in the androgenic mouse model [ 71 ]. A reduced level of PKM2 was observed in testosterone-treated mice, while elevated expression of this protein occurred in the androgenic mice, regrowing hair after treatment with minoxidil (1%, w / w ), AA in ethanol (1%), and AA–TF#15 (1%).…”
Section: Discussionmentioning
confidence: 99%
“…The lysates were centrifuged at 15,000 rpm for 30 min. An equal amount of each protein was incubated with reaction buffer (100 mM KCl, 50 mM Tris, pH 7.5, 5 mM, 0.6 mM ADP, 0.5 mM phosphoenolpyruvate (PEP), 10 µM fructose-1,6-bisphosphate (FBP), 240 µM NADH, and 8 units of lactate dehydrogenase (LDH), as previously described [ 22 ]. The change in absorbance at 320 nm owing to the oxidation of NADH was measured using a FLUOstar OPTIMA luminometer (BMG Labtech, Offenburg, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…We confirmed that TEPP-46, a PKM2 activator, promoted the migration of human keratinocytes and wound healing in mice. Moreover, combination treatment with TEPP-46 and KY19382, a small molecule that activates Wnt/β-catenin signaling by interfering with cytosolic CXXC-type zinc finger protein 5 (CXXC5) function via CXXC5-Dishevelled interaction [ 22 ], significantly enhanced wound healing, followed by re-epithelialization and collagen deposition. PKM2 and its activity were highly increased in the wound sites by cotreatment.…”
Section: Introductionmentioning
confidence: 99%